Health-Promoting Lifestyle of Breast Cancer Patients and Family Members in a Chinese Genetic Counseling Clinic: A Cross-Sectional Study - Shengqun Hou; Liqin Chen; Xiaofang Lu; Cuixia Fu; Qianqian Yu; Tingting Su; Jiajia Qiu; Yun Li; Zhenqi Lu (IMR Press, 2022)
Background: Risk management strategies play a significant role in genetic counseling, which involves lifestyle modification with respect to nutrition and unhealthy living habits, enhanced screening imaging, endocrine therapy, and following the physician's advice etc. This study aimed to describe the health-promoting lifestyle of breast cancer patients and their family members in a Chinese genetic counseling clinic, and to explore its various levels encompassing different socio-economic variables. Methods: This was a cross-sectional study. The participants in this study originated from a genetic counseling clinic of a cancer center in Shanghai, China. Two hundred and fifty nine patients conforming to the inclusion and exclusion criteria were screened from November 2019 to March 2022. Participants agreeing to participate were sent a questionnaire web-link with an invitation to finish this survey. Two questionnaires were included in the link, one referring to socio-economic information and the other referring to the health-promoting lifestyle. Chinese Health-promoting lifestyle profile-Ⅱ (HPLP-Ⅱ) was used to evaluate the health-promoting lifestyle. Results: One hundred and forty participants were finally included in this study. The mean scores for health-promoting lifestyle was 141.22 ± 19.77, and multiple liner regression revealed monthly family income to be a statistically significant predictor of health-promoting lifestyle (p < 0.05). In the six subscales, health responsibility got the highest score (26.43 ± 4.40), and nutrition received the lowest score (17.81 ± 4.73). Self-actualization was 25.84 ± 4.19, physical activity 24.02 ± 4.97, interpersonal relationship 22.21 ± 4.42, and stress management 24.91 ± 4.39. Conclusions: A representative level of health-promoting lifestyle of breast cancer patients and family members in a Chinese genetic counseling clinic were acquired. More education and intervention should be tailored to enhance and encourage health-promoting lifestyle behaviors in participants with low monthly family income. Additionally, developing nutritional curriculum and strengthening the publicity of nutritional popular science are priorities for future improvement measures.